2010
DOI: 10.1016/j.biopsych.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Causes Amygdala Hyperexcitability in Rodents

Abstract: Background-Chronic stress is a major health concern, often leading to depression, anxiety or when severe enough, post-traumatic stress disorder (PTSD). While many studies demonstrate that the amygdala is hyper-responsive in patients with these disorders, the cellular neurophysiological effects of chronic stress on the systems that underlie psychiatric disorders, such as the amygdala, are relatively unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
193
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(224 citation statements)
references
References 68 publications
20
193
1
4
Order By: Relevance
“…For instance, increased excitatory responses to glutamate and increased glutamatergic synaptic transmission. The increased excitatory response to glutamate could be caused by increased neuronal membrane excitability (Rosenkranz et al, 2010;Hetzel and Rosenkranz, 2014), increased function of NMDA or AMPA receptors (Adamec et al, 2005;Caudal et al, 2010;Mozhui et al, 2010;Suvrathan et al, 2014), reduced glutamatergic drive of GABAergic networks (Masneuf et al, 2014), or upregulation of glutamatergic receptors (Lei and Tejani-Butt, 2010;Gan et al, 2014). Increased glutamatergic synaptic transmission could be caused by increased glutamatergic inputs, as observed here and in other studies (Mitra et al, 2005;Vyas et al, 2006;Padival et al, 2013Padival et al, , 2015Suvrathan et al, 2014;Tsai et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…For instance, increased excitatory responses to glutamate and increased glutamatergic synaptic transmission. The increased excitatory response to glutamate could be caused by increased neuronal membrane excitability (Rosenkranz et al, 2010;Hetzel and Rosenkranz, 2014), increased function of NMDA or AMPA receptors (Adamec et al, 2005;Caudal et al, 2010;Mozhui et al, 2010;Suvrathan et al, 2014), reduced glutamatergic drive of GABAergic networks (Masneuf et al, 2014), or upregulation of glutamatergic receptors (Lei and Tejani-Butt, 2010;Gan et al, 2014). Increased glutamatergic synaptic transmission could be caused by increased glutamatergic inputs, as observed here and in other studies (Mitra et al, 2005;Vyas et al, 2006;Padival et al, 2013Padival et al, , 2015Suvrathan et al, 2014;Tsai et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Studies have repeatedly demonstrated that the increased activity of the amygdala in adult male rats after stress parallels increased anxiety (Vyas et al, 2004;DoremusFitzwater et al, 2009;Rosenkranz et al, 2010) and production of behaviors that rely on the BLA, such as such as freezing in response to a fear-conditioned cue (Conrad et al, 1999;Rau et al, 2005;Rodriguez Manzanares et al, 2005;ToledoRodriguez and Sandi, 2007;Atchley et al, 2012;Zhang and Rosenkranz, 2013). Relatively less is known about the effects of stress on amygdala-dependent behaviors in adolescents; however, in several studies increased fear conditioning is accompanied by an impairment of fear extinction in adolescents and enhanced generalization of fear (Morrissey et al, 2011;Zhang and Rosenkranz, 2013;Muller et al, 2014;Padival et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the functional roles of specific brain regions in emotional processing, neuropathological abnormalities observed in depression suggest that areas that mediate autonomic and neuroendocrine responses (amygdala) is associated with increased activity and cerebral blood flow, while reduction in activity is observed in brain regions that control emotional processing (cortex) (Manji et al, 2001). Antidepressant treatment reduces CBF and metabolism in the amygadala (Drevets, 2000b;Drevets et al, 1999), attenuating hyperresponsiveness to stress (Rosenkranz et al, 2010). Similarly, larger hippocampal volume (Frodl et al, 2008;Kronmuller et al, 2008;MacQueen et al, 2008) and gray matter density in the ACC (Costafreda et al, 2009) were positively correlated with antidepressant response.…”
Section: Neurostructural and Neurofunctional Studiesmentioning
confidence: 99%